2020
DOI: 10.1039/d0bm00549e
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal augment stromal disrupting effects for enhanced Abraxane synergy chemotherapy in pancreatic cancer PDX mode

Abstract: Preparation of Abraxane@MoSe2 and its PTT effect augment stromal disrupting effects for enhanced Abraxane synergy chemotherapy in pancreatic cancer PDX mode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…In recent years, with the rapid development of nanotechnology, various nanoprobes with unique properties have provided new opportunities for tumor diagnosis and treatment [ 9 15 ]. To break through the dense fibrous stroma of pancreatic cancer, plenty of studies have been explored with different strategies, such as depleting the glycans in matrix membrane, reducing the production of stromal cells via inhibition of signal pathway, and fibrous matrix loosen through photothermal nanoprobes [ 16 18 ]. When it comes to drug resistance, there are complex mechanisms related, such as aberrant gene expression, deregulated signal pathways, and regulated rate-limiting enzymes, while nanoprobes also exhibit promising in drug-resistance overcoming [ 19 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the rapid development of nanotechnology, various nanoprobes with unique properties have provided new opportunities for tumor diagnosis and treatment [ 9 15 ]. To break through the dense fibrous stroma of pancreatic cancer, plenty of studies have been explored with different strategies, such as depleting the glycans in matrix membrane, reducing the production of stromal cells via inhibition of signal pathway, and fibrous matrix loosen through photothermal nanoprobes [ 16 18 ]. When it comes to drug resistance, there are complex mechanisms related, such as aberrant gene expression, deregulated signal pathways, and regulated rate-limiting enzymes, while nanoprobes also exhibit promising in drug-resistance overcoming [ 19 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…This simple and effective method has been widely used for preparing Mo-NMs in recent years. [100][101][102]115,116,143,[147][148][149][150] As a typical example, Zhang et al first used this method to exfoliate bulk TMD crystals, including MoS 2 and MoSe 2 , into single-or few-layer nanosheets by sonicating them in polyphenol for 2 h (Figure 2A). [147] Similarly, Lei et al reported the preparation of MoSe 2 nanosheets via this method by sonicating MoSe 2 bulk crystal in PVP aqueous solution.…”
Section: Sonication-assisted Liquid-phase Exfoliationmentioning
confidence: 99%
“…[ 101 ] One of the big advantages of this strategy is that in situ surface modification of MoSe 2 with PVP can be realized during the preparation process. Therefore, this method was widely explored to prepare MoSe 2 nanosheets as well as MoO 3− x nanoflakes [ 143,149 ] (Figure 2B,C) by some other groups (Figure 2D). [ 150 ] It should be noted that the polymer and experimental conditions selected for sonication might be different in different literature.…”
Section: Classification Preparation and Surface Modification Of Mo‐nmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mild HT applied to spheroids of pancreatic cancer cells (Panc1) and fibroblasts (WI 38) significantly decreased the amount of intact collagen fibers, with a coinciding decrease in spheroid volume and cell viability by apoptotic and necrotic processes[ 14 ]. Local HT through the use of a photothermal agent combined with a photothermal-chemotherapeutic agent (Abraxane@Mose 2 ) and subsequently irradiated by a laser beam could disrupt tissue architecture and reduce the number of carcinoma-associated fibroblasts (CAFs), subsequently enhancing the efficacy of Abraxane in a mouse model of PDAC[ 27 ]. Similarly, in a mouse model of cholangiocarcinoma, a nanoheater used for PTT (multifunctional iron oxide nanoflowers decorated with gold particles) with high uptake by CAFs produced a significant depletion of CAFs as well as a reduction in tumor stiffness followed by significant tumor regression[ 28 ].…”
Section: Htmentioning
confidence: 99%